Moral Issues in the Natural Sciences and Technologies - Boshoff, Hendrik (AOSIS, 2019)
This book reflects academically on important and relevant natural scientific disciplines, important technologies and related media to determine and communicate the moral issues and challenges within those specific fields of study, and how to deal with them morally and from a multidimensional South African context. It aims to add scientific, technological and ethical value, locally and globally, by reflecting mainly from the viewpoint of a specific scholars, writing about the most pressing moral issues or challenges raised by problems within their specific field of study. It is written mainly from a qualitative methodological perspective, including autobiographical and participatory views. The co-authors present in respective chapters their research systematically and intersectionally, based on profound theoretical analysis and reasoning. Current research in the basic and implied sciences and technologies requires sound ethical practice based on a defensible moral stance. Moral norms, in our view, are deeply grounded and evolved convictions about justice and injustice, right and wrong, good and bad. It is not about rules. This scholarly book combines the insights and expertise of established South African scholars from different disciplines and backgrounds. The contributors are all deeply committed to the value and validity of science and ethical practice across the moral spectrum. Open and responsible discussions around this topic can lead to the introduction of moral guidelines and regulations to protect the rights of individuals, animals and the environment, while simultaneously facilitating the growth of scientific practice. This collected work, with its very specific and carefully selected grouping of academic fields, aims to innovatively assist in alleviating the shortage of academic publications reflecting on the moral issues in these specific fields.